Analisis Wacana Presiden Tiga Periode Perspektif Van Dijk Di Instagram Tvonenews - Heny Triyaningsih; Moh Nor Abrori (STISIP Widyapuri Mandiri Sukabumi, 2023)
The researchers carried out the analysis was on news related to the three-term presidential discourse on the Instagram Tvonenews study 22 and 26 March 2021 using Van Dijk's critical discourse analysis model. Based on this, there are 2 research focuses that the researcher will do here. First, how is the text structure of the three-term Presidential discourse on Tvonenews Instagram, second, how is social cognition and social context in the three-term Presidential discourse on Tvonenews Instagram. This study uses a qualitative research approach. Meanwhile, the type of research is library research. This study discusses the text, social cognition and social context of Tvonenews' Instagram posts related to the three-term Presidential discourse using the theory of critical discourse analysis by Teun A. Van Dijk. The source of the data that the researcher obtained was through the process of documentation and observation from Tvonenews Instagram posts related to the three-term presidential discourse.